Microalgae based biodiesel production – current and future scenario - Sahay, Sudha; Braganza, Vincent J (Journal of Experimental Sciences, 2016)
Microalgae have a clear potential to be used as a source for the production of biofuel. In order to utilize microalgae for this purpose, the most common systems for cultivating and harvesting them are investigated in the previous years. Since there are many species of microalgae with varying lipid accumulating characteristics, a diversity of options for the production of microalgae based energy have been analyzed. Subsequently, the energy inputs and conditions needed for growing and harvesting the microalgae and its oil production potentials are examined. This concludes with a formulation of complete concept for producing a renewable energy carrier from microalgae, which will be used for in-depth analysis. Â